LEGAL PROTECTION FOR THE PUBLIC ON POSITIONAL ABUSE FOR CORRUPTION OFFENCES - Gimnastiar, Muhammad Alam; Sugiharto, Dr. (YURIS: Journal of Court and Justice, 2023)
The reasons for a public official to commit corruption may be varied, but generally known as the GONE theory (Greedy, Opportunity, Need, Exposure) as proposed by Jack Bologna. Corruption leads to a deceleration of the country’s economic growth, decreased investment, increased poverty and increased income inequality. Corruption not only affects the country, but also the whole society. The impacts of corruption on various aspects can be perceived by the public. Therefore, this research is conducted to determine the application of the law against public officials who are corrupt, to analyse the juridical mechanism in public malfeasance, and to analyse court decisions on corruption committed by public officials. The type of research used is juridical normative combined with a statutory approach, conceptual approach, analytical approach, and case study approach. There are 3 legal sources used, such as (1) primary legal sources consist of laws and regulations related to the research topic; (2) secondary legal sources consist of books, law journals, and legal dictionaries; (3) tertiary legal sources consist of internet media, print media, and mass media. The implementation of anti-corruption values to the community is based on needs such as honesty, discipline, responsibility, simplicity, and justice. Improving applicable laws and regulations, improving bureaucratic reform governance, creating an anti-corruption work environment, applying clean and good governance principles, and utilising transparency technology are some of the efforts to prevent corruption in society.